ANALISIS STRATEGI MASUK PASAR SKIN CARE DEWI GRIYA DI DAERAH BEKASI - , Aldi Purwandi, Ely Susanto, SIP, MBA, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Skin care industry is categorized as a potential industry. This industryâs main concern is about beauty and cosmetics. This Industry is rapidly growing throughout the world, including Indonesia. Indonesia is recognized as one of the fastest â growing global markets for cosmetic and toiletries. The turnover and market growth is always increasing each year. Dewi Griya is a skin care company located in Bekasi Area, which was established since 1991 and still growing in recent times. To be exist in this industry for more than 20 years is not an easy achievement, yet proving that Dewi Griya has excellent competences and trusted by the community surrounded Bekasi Area. A good company, should have a maximum and adequate competitive strategies. The competitive strategy can be obtained by business activities within the company, in accordance with the objectives that have been planned by the company in achieving its vision and mission. This study aims to describe the competition of skin care industry and positioning of Dewi Griya among competitors and skin care industry sector mainly in Bekasi Area, which is one of the oldest established companies in that area. This study is also aiming to analyze internal and external condition of the company, and form what kind of strategies can be assessed by Dewi Griya to expand the market. Across this study, it will also be seen the resources and determining factors, which are the competitive advantage for the company. To Analyze what have been described above, This study uses tools of Matrix EFE and IFE, Porter Five Forces, Resources and Capabilities Analysis, Matrix IE, and Matrix SPACE. All tools will construct companyâs strength and weakness as well as the strategic positioning for the company to generate strategic decision, which is suitable for each position. The result from this study indicates that Dewi Griya almost has every competitive advantage that is important for the company as well as the positioning above all its competitors, of course those are good competitive advantages for the industry. Dewi Griya also has a good quadrant position to always grow aggressively. That position will make an impact for options in strategic making decision as well as a combination with any other strategic decisions and also supported by strong cash flow and financial condition for the company.